Dietary manipulation of brown adipose tissue (BAT) thermogenesis in healthy adult volunteers - Vazquez Rocha, Lucia del Carmen (2019)
Brown adipose tissue (BAT) is one of the three different types of adipose tissues found in mammals and is only present in small amounts in the adult human (~100 g), of which the main site is the supraclavicular neck region. As BAT possess a unique mitochondrial uncoupling protein (UCP1), it can have a pronounced influence on energy balance due to the capacity of UCP1 to uncouple aerobic respiration that results in the free flow of protons across the inner mitochondrial membrane thereby bypassing the need to convert ADP to ATP. One of BAT’s main functions is to transfer energy from food into thermal energy, and this is primarily regulated through the sympathetic nervous system (SNS). The activation of non-shivering thermogenesis in BAT can be measured indirectly by thermal imaging (TI). Two important factors that influence the activity of BAT are diet and cold. My thesis aimed to investigate the effect of cold and individual dietary compounds, i.e. galacto-oligosaccharide (GOS) prebiotic and extra virgin olive oil (EVOO) on BAT thermogenesis in healthy adult volunteers by using TI. In mice, the end product of microbial fermentation of the GOS-prebiotic, short chain fatty acids (SCFA), and the phenol content in EVOO (oleuropein aglycone) have both been shown to increase UCP1 expression in BAT, and therefore, promote thermogenesis.